Closed‐loop technology: a practical guide. (2nd August 2021) - Hartnell, Sara; Fuchs, Julia; Boughton, Charlotte K; Hovorka, Roman
Abstract: Hybrid closed‐loop insulin delivery has been shown to be safe and effective in improving time in target glucose range and reducing the risk of hypoglycaemia for people with type 1 diabetes. Benefits in terms of reduction in diabetes burden have also been demonstrated. After decades of research and development, four hybrid closed‐loop systems are now commercially available in the UK with more expected soon. We review the hybrid closed‐loop systems currently available – Tandem t:slim with Control‐IQ, CamAPS FX, Medtronic MiniMed 670G and second generation, Medtronic MiniMed 780G – and discuss the components and key features of these technologies. As hybrid closed‐loop systems become more widely available, education and training of health care professionals and users will be pivotal in ensuring the research benefits are translated into real‐world outcomes. Users need to be supported to make appropriate choices about the different systems available and be guided in realistic expectations regarding outcomes. Attention must be given to the key training and education requirements and how these differ from traditional insulin pump therapy. Training and interpretation in reviewing closed‐loop data are essential for post‐initiation reviews and optimisation. Developments in diabetes technology are progressing rapidly and other hybrid closed‐loop systems currently in pivotal clinical trials may soon become commercially available. We also consider other important progress in this field including the use of faster‐acting insulin analogues, adjunctive therapies such as SGLT2 inhibitors and dual hormone closed‐loop systems. Copyright © 2021 John Wiley & Sons.